Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri 31 Padang - RISKA MAHARANI (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills are one of the goal of mathematics learning that must be achieved by students. But in the reality at SMP Negeri 31 Padang this ability is still not optimal and do not facilitated yet for improving those skill well. One effort to overcome these problems is to apply the the Two Stay Two Stray (TSTS) cooperative learning model. The purpose of this study is to describe whether the mathematical communication skills of student who learn by using the TSTS model is more better than student who learn by conventional learning. This type of research is quasi-experimental and descriptive research design with Randomized Control Group Only Design. Based on the results of data analysis, the mathematical communication skills of student who learn by applying the TSTS learning model is more better than the mathematical communication skills of student who learn by applying the conventional  learningKeywords – Cooperative Learning ,Mathematical Communication Skills, Two Stay Two Stray